Präfixverben in einer mehrstufigen Analyse - Versuch einer Modellierung unter konfrontativem Blick - Schröder, Jochen (Studia Germanica Posnaniensia, 2018)
In reference to requirements and needs of foreign language teaching the author, motivated by the requirements and needs of methodology of foreign language teaching, performs a confrontative analysis of prefixal verbs of the German language and their Polish equivalents and proves that word-formation studies must be extended with a syntactic aspect since inter-language differences are manifested in an actual usage (on the surface structure).